Association of the Triglyceride-Glucose Index with Severity of Coronary Artery Disease in Patients Undergoing Coronary Angiography for Ischemic Heart Disease - Poudel, Samir Kumar; Khanal, Shambhu; Lamsal, Lekhnath; Koirala, Prabha; Sherpa, Kunjang; Gautam, Binayak; Mishra, Deepak Kumar; Poudel, Lata Gautam (Nepalese Heart Journal, 2026)
Background: Coronary artery disease (CAD) remains the most prevalent cause of morbidity and mortality worldwide. The triglyceride glucose (TyG) index is a simple and surrogate marker of insulin resistance (IR) which has been linked to the severity of CAD in multiple international studies. Nevertheless, its correlation with angiographic severity of coronary artery disease (CAD) in the Nepalese population has not been established so far. This study aimed to evaluate the relationship between the TyG index and CAD severity quantified by the Gensini score in patients who underwent coronary angiography for ischemic heart disease. Methods: This is a cross-sectional observational study conducted in the Department of Cardiology, NAMS Bir Hospital, Kathmandu. One hundred and one consecutive patients (mean age 64.17 ± 10 years; 55.4% male) undergoing coronary angiography for ischemic heart disease were enrolled. Fasting venous blood samples were taken for determination of glucose and triglyceride levels. The TyG index was calculated as ln (fasting triglycerides [mg/dL] × fasting glucose [mg/dL] / 2). Coronary angiograms were assessed with Gensini scoring system. Spearman’s correlation test was employed to assess correlation between variables. Statistical significance was set at p < 0.05. Results: Demography of the patients was analyzed (mean age 64.17 ± 10 years; 55.4% male); the majority belonged to the middle-aged group (54 patients, 53.5%). Hypertension was the most prevalent comorbidity (60.4%), followed by diabetes (33.7%) and smoking (25.7%). On coronary angiography, 43 patients (42.6%) had normal coronaries, 17 (16.8%) had minor coronary artery disease (CAD), 16 (15.8%) had single vessel disease, 17 (16.8%) had double vessel disease, and 8 (7.9%) had triple vessel disease. A statistically significant positive correlation was observed between the TyG index and the Gensini score (r = 0.208, p = 0.037). A similarly significant positive correlation was found between the TyG index and the presence of CAD (r = 0.217, p = 0.029). Conclusions: The TyG index was significantly associated with the severity of CAD as measured by the Gensini score, but this association was modest. This simple and cost-effective biomarker may help clinicians stratify risk for patients with ischemic heart disease, especially in resource-limited settings where advanced metabolic testing is unavailable. Further prospective studies in Nepal are warranted to validate these findings and to establish population specific TyG cutoff values.